Gagal Jantung Kanan pada Hipertiroid Tidak Terkontrol: Laporan Kasus - Lazuardy, Kevin; Nainggolan, Leonard; Tedyanto, Nadim Marchian (Jurnal Penyakit Dalam Indonesia, 2026)
Right heart failure is a clinical syndrome that is influenced by various factors. The incidence of heart failure reaches 5/1,000 population, while the prevalence of heart failure reaches 1-2% of the adult population. Management of the main etiology of heart failure is the main therapy. In some cases, hyperthyroidism is an indirect cause of heart failure, especially in right heart failure. Hyperthyroidism can cause reversible pulmonary hypertension which causes right heart failure, although the underlying mechanism is uncertain at the moment. This study reports a 46-year-old woman who was diagnosed with right heart failure and also had hyperthyroidism. In this case, hyperthyroidism was not detected because there were no typical symptoms in the patient. The patient was given furosemide intravenous, propylthiouracil, and bisoprolol. After clinical improvement, the patient went home with right heart failure in uncontrolled hyperthyroidism as a final diagnosis.